Psychosis and cannabis (Archives of Clinical Psychiatry, 2005)
Alcohol and cannabis misuse is currently the most frequent co-morbidity disorder of schizophrenia. The following four issues will be dealt with: 1) the neurobiological basis of the psychosis-inducing, pathogenic effects of THC, the agent contained in cannabis products. 2) Can cannabis use - and for comparison alcohol abuse - prematurely trigger or even cause schizophrenia? 3) Are persons genetically liable to schizophrenia, psychosis-prone individuals or young persons before completion of brain development at an increased risk? 4) What consequences does cannabis use have on the symptomatology and further course of schizophrenia? Results from recent literature and the ABC Schizophrenia Study show that the risk for cannabis use in schizophrenia is about twice the size in healthy controls. In most cases cannabis use starts before first admission, in a third of cases before schizophrenia onset. There is an increased affinity to misuse already at the prodromal stage. Cannabis can prematurely trigger schizophrenia onset - on average eight years earlier than in non-use - and cause the illness partly in interaction with predisposing factors. Cannabis use in the course of schizophrenia increases positive symptoms and reduces affective flattening, thus leading to dysfunctional coping in some cases.